0D, 1D, and 2D Supramolecular Nanoassemblies of a Porphyrin: Controllable Assembly, and Dimensionality‐Dependent Catalytic Performances. (25th February 2021) - Li, Peng; Xu, Guojing; Wang, Nannan; Guan, Bo; Zhu, Shuiqing; Chen, Penglei; Liu, Minghua
Abstract: While tremendous advances have been made in dimensionality‐dependent performances of inorganic‐based low‐dimensional nanostructures, paradigms concerning π‐conjugated molecule‐based supramolecular nanoassemblies are relatively fewer despite their various intrinsic advantages. It is herein reported that 0D, 1D, and 2D supramolecular nanostructures of a porphyrin, 5, 10, 15, 20‐tetrakis(4‐aminophenyl)‐21H, 23H‐porphine, with a spherical, fibrous and sheetlike architecture, respectively, could be fabricated via a reprecipitation protocol. As a typical example to demonstrate their dimensionality‐dependent optoelectronic performances, it is shown that the nanomaterials could serve as photocatalysts for water remediation, where the catalytic reactivity exhibits a trend of nanofibers> nanospheres> nanosheets. The superior catalytic reactivity of the nanofibers stems from the formation of relatively well‐defined J‐aggregates with orderly and tightly organized chromophores, conferring them with strong photoinduced electron–hole transport and separation capability. The higher catalytic reactivity of the nanospheres than nanosheets results from their larger specific surface area, which facilitates efficient accessibility of photogenerated charge carriers, although the porphyrins therein form unspecific J‐aggregates with disorderly and loosely stacked chromophores. The investigation likely initiates a simple method for π‐conjugated molecule‐based 0D, 1D and 2D nanoassemblies by using the same tectons, based on which the highlighted underlying scientific insights might provide useful clues for rational design of organic‐based low‐dimensional advanced soft materials. Abstract : 0D, 1D, and 2D supramolecular nanoassemblies of a porphyrin with a spherical, fibrous, and sheet‐like structure, respectively, are fabricated. Their photocatalytic reactivity displays an order of nanofibers>nanospheres>nanosheets. The formation of J‐aggregates with distinct chromophore arrangements plays an important role in such fascinating dimensionality‐dependent performances. The highlighted scientific insights provide useful clues for the rational design of organic‐based low‐dimensional advanced optoelectronic materials.